Studies on the application of Myceliophthora thermophila JCP1-4 cellulases cocktail on sugarcane bagasse pretreated by different methods - Travaini, Rodolfo; Pereira, Josiani De Cassia [UNESP]; Zavarizi, Franco [UNESP]; Bocchini Martins, Daniela Alonso [UNESP]; Gomes, Eleni [UNESP]; Rodriguez Bolado, Silvia (Elsevier B.V., 2014)
The hydrolysis step for sugar production in biorefineries is crucial for the sequential processes involved and cellulases cocktails behave differently according to the pretreatment employed. In this study, the application of the cellulases cocktail produced by the fungus Myceliophthora thermophila JCP1-4 was studied on the saccharification of sugarcane bagasse pretreated by ozonolysis and thermic ferric nitrate (TFN), and the results were compared with commercial enzymes (Novozymes Celluclast 1.5L, Novozym 188). The fungal cellulases cocktail hold an activity of FPU:β-glucosidase of 1:4(U/mL); time, temperature, FPU by g of cellulose load and percentage of dry matter (DM) were studied. The analysis of central composite design of TFN pretreated showed that fungal cellulases works better in DM values of 3–3.5% (4.5% for commercial), temperatures higher than 50 °C (<45 °C for commercial) and 15FPU for both; commercial enzymes yielded 7.78 g/L of reducing sugars and the fungal enzymes 5.42 g/L. With the ozone pretreated, the fungal enzymes presented a higher thermostability with faster kinects, being able to produce 5.56 g/L of reducing sugars (60 °C, 8 h), against 5.20 g/L for commercial enzymes (50 °C, 24 h), (10FPU, 3%DM for both). The FPU derivate analysis revels better yields with 7.5FPU, and the increase of DM to 7.5% resulted 13.28 g/L of reducing sugars.